REPRESENTASI ATRIBUT SIMBOLIK DALAM FILM BADRUN & LOUNDRI KARYA GARIN NUGROHO: ANALISIS WACANA KRITIS - Nabiilah, Lailla; Nurrachmi Febriyanti, Syafrida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Film functions not only as a medium of entertainment but also as a space for the production of meaning that represents social reality through various symbols. This study aims to analyze the symbolic attributes portrayed in Badrun & Loundri, directed by Garin Nugroho, and to reveal the meanings, ideologies, and social criticism constructed through these symbolic representations. This research employs a qualitative approach using Teun A. van Dijk's Critical Discourse Analysis framework, which examines three dimensions: text structure, social cognition, and social context. The data were collected through observation of selected scenes in the film, documentation, and a review of relevant literature. The findings indicate that symbolic attributes, including religious clothing, police uniforms, volunteer vests, masks, and ordinary clothing, function not only as markers of identity but also as sources of social legitimacy that shape public trust and authority. The film demonstrates that legitimacy is often constructed through visual symbols rather than personal integrity, thereby creating opportunities for the manipulation of power, image-building, and the abuse of public trust. Through these representations, Garin Nugroho criticizes society's tendency to associate appearance with morality, authority, and truth without engaging in critical evaluation. Therefore, Badrun & Loundri serves not only as a representation of social reality but also as a medium for reflecting on the practice of symbolic legitimacy within Indonesian society.